Analysis of Threats and Attacks Impacts on Smart Grid Networks - Horálek, Josef; Holík, Filip (My University, 2017)
This paper introduces the results of theoretical and practical analysis of threats and attacks on Smart Grid networks. Authors introduce Smart Grid as a complex system composed from two basic subsystems. These subsystems have characteristics of pure data networks and grid networks. Due to the fact that these subsystems are interconnected into one complex Smart Grid system, it was necessary to conduct an analysis of their interrelations. A company focused on power distribution (located in the Czech Republic) was consulted about these relations and their influence on security. The paper also introduces analysis of reasons to conduct attacks on SG networks. Analysis also describes impacts of the most basic attacks on data networks, from the Smart Grid networks’ point of view. The main contribution of the analysis is its practical impact on functionality of the whole Smart Grid and verification of the results within the complete Smart Grid environment.
Analýza hrozeb a dopadů útoků na Smart Grid Sítě
Keywords: DDoS; IP spoofing; MAC address flooding; Smart Grid attacks; Smart Grid networks; Smart Grid security; DDoS; IP spoofing; MAC address flooding; Smart Grid útoky; Smart Grid sítě; Smart Grid bezpečnost